2019
DOI: 10.3389/fpsyg.2019.00877
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries Between Direct and Indirect Scalar Implicatures in Second Language Acquisition

Abstract: A direct scalar implicature (DSI) arises when a sentence with a weaker term like sometimes implies the negation of the stronger alternative always (e.g., John sometimes (∼ not always) drinks coffee). A reverse implicature, often referred to as indirect scalar implicature (ISI), arises when the stronger term is under negation and implicates the weaker alternative (e.g., John doesn’t always (∼ sometimes) drink coffee). Recent research suggests that English-speaking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…For example, De Neys and Schaeken (2007) show that participants compute fewer scalar implicatures when they are under a higher processing load (e.g., Bott and Noveck, 2004;Marty et al, 2013), which might be a result of the strengthened meaning not actually being activated. Feng and Cho (2019) RT demonstrate that nonnative speakers in contrast to native speakers do not compute indirect scalar implicatures (e.g., not always → sometimes), which might be due to working memory limitations or insufficient linguistic competence in L2. An explanation in terms of linguistic competence would be compatible with findings for children, for whom it has been shown that they do not compute implicatures if they do not know the linguistic expressions denoting the relevant alternatives, which is often the case for quantifiers (e.g., Barner et al, 2011;Horowitz et al, 2018), or if they do not perceive an alternative as relevant (Skordos and Papafragou, 2016).…”
Section: The Nature Of the Activation Process (Mandatory Or Strategic)mentioning
confidence: 81%
See 1 more Smart Citation
“…For example, De Neys and Schaeken (2007) show that participants compute fewer scalar implicatures when they are under a higher processing load (e.g., Bott and Noveck, 2004;Marty et al, 2013), which might be a result of the strengthened meaning not actually being activated. Feng and Cho (2019) RT demonstrate that nonnative speakers in contrast to native speakers do not compute indirect scalar implicatures (e.g., not always → sometimes), which might be due to working memory limitations or insufficient linguistic competence in L2. An explanation in terms of linguistic competence would be compatible with findings for children, for whom it has been shown that they do not compute implicatures if they do not know the linguistic expressions denoting the relevant alternatives, which is often the case for quantifiers (e.g., Barner et al, 2011;Horowitz et al, 2018), or if they do not perceive an alternative as relevant (Skordos and Papafragou, 2016).…”
Section: The Nature Of the Activation Process (Mandatory Or Strategic)mentioning
confidence: 81%
“…Nordmeyer and Frank, 2014). Feng and Cho (2019) RT compared direct and indirect scalar implicatures (sometimes → not always; not always → sometimes) for native speakers of English and L2 English learners with a covered box paradigm. Participants were presented with a visible picture and an invisible one (the covered box) and chose either, depending on the meaning they assign to a sentence they hear.…”
Section: Alternatives For All? Individual Differencesmentioning
confidence: 99%
“…However, the scalar inference can be cancelled in Speaker B's utterance in (7)(8). By employing a covered-box experiment, Feng and Cho (2019) examined L1-Chinese L2-English speakers' computation and suspension of the scalar expressions sometimes and not always. They found that L2 speakers computed and suspended the inference of sometimes at a native-like level; however, the inference of not always posed difficulties to L2 speakers, especially the suspension of not always which involved calculation and processing alternative meanings.…”
Section: L2 Acquisition At the Semantics-pragmatics Interfacementioning
confidence: 99%
“…Other studies challenging the Interface Hypothesis have suggested that linguistic properties at external interfaces, especially at the syntax–discourse interface, are acquirable by L2 learners to a native-like level, despite possible delays (Destruel and Donaldson, 2017; Ivanov, 2012; Rothman, 2009). Since the first publication investigating L2 acquisition of scalar implicatures at a new interface, namely, the semantics–pragmatics interface (Slabakova, 2010), several attempts have been made to suggest that computing scalar implicatures is not a problem for L2 speakers (Feng and Cho, 2019; Lieberman, 2009; Miller, et al, 2016; Slabakova, 2010; Snape and Hosoi, 2018). In fact, L2 speakers are more likely to generate scalar inferences than native speakers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of work that has focused on how scalar inferences are given rise to before their manifestation in the form of judgment response. Reports are mainly split into two camps; one is placing emphasis on the proposition that sentences with scalar implicatures carry processing costs (e.g., [2,12,18,20,31,35,37,74]), and the other placing emphasis on that pragmatic processing is not associated with any cognitive load (e.g., [3,15,16,47,75]). These results were to a large extent discussed in the light of two psychological theories which envisage opposing views about how logical and pragmatic interpretations unfold prior to their manifestation in the form of a response: the default theory [10] and the relevance theory [11].…”
Section: Processing Time Of Pragmatic Interpretations Of Scalar Implicaturesmentioning
confidence: 99%